CORB is the best pneumonia severity score for elderly hospitalised patients with suspected pneumonia. Issue 6 (June 2014) - Williams, E.; Girdwood, J.; Janus, E.; Karunajeewa, H.
Abstract Pneumonia severity scoring systems have been developed to identify patients at highest mortality risk, and are used in guidelines to limit use of broad‐spectrum antibiotics to patients with severe community‐acquired pneumonia. A retrospective audit of hospitalised general internal medicine patients with pneumonia was performed to assess the diagnostic performance of various pneumonia severity scores in an elderly general internal medicine population.